Étude sur les effets de la gymnastique prénatale sur les courbures de la colonne vertébrale auprès de 120 femmes de la ville de Porto - Novo - Abessolo, Henriette Magali; LAWANI, MOHAMED MANSOUROU; Houeto, Gracien; AKPLOGAN, B (My University, 2016)
Woman body undergoes postural changes during pregnancy process. These changes may impact on their physical conditions and lead to some limitations in daily activities. The aim of this research work is to evaluate the effect of a prenatal gymnastics program on changes in spinal curvature in pregnant women at Porto-Novo. Concerning methods, 120 women constituted the sample of the study, comprised of recruited purposive and divided into three groups: 32 pregnant women using antenatal gymnastics twice a week for eight weeks, 48 sedentary pregnant women and 40 sedentary non-pregnant women. The measurement of spinal curvatures took place at the beginning and the end of the study using with flexible ruler of mark Morn sun. The results showed that thoracic kyphosis and lumbar lordosis have increased and are significantly different between the three groups. These results suggest that prenatal gymnastics during pregnancy acts on the curvatures of the spine minimizing their emphasis. Summary During pregnancy, the female body undergoes postural changes. These changes can impact on physical health and lead to limitations during everyday activities. This study evaluated the effect of prenatal gymnastics program on changes in spinal curvature in pregnant women in Porto-Novo. The sample was comprised of 120 women recruited purposive and divided into three groups: 32 pregnant women using antenatal gymnastics twice a week for eight weeks, 48 sedentary pregnant women and 40 non-sedentary pregnant women. The measurement of spinal curvature was carried out at the beginning and end of the study using a flexible rule Morn sun brand. The resultant obtained show that thoracic kyphosis and lumbar lordosis increased and are significantly different between the three groups. These results suggest that prenatal gymnastics during pregnancy acts on thWoman body undergoes postural changes during pregnancy process. These changes may impact on their physical conditions and lead to some limitations in daily activities. The aim of this research work is to evaluate the effect of a prenatal gymnastics program on changes in spinal curvature in pregnant women at Porto-Novo. Concerning methods, 120 women constituted the sample of the study, comprised of recruited purposive and divided into three groups: 32 pregnant women using antenatal gymnastics twice a week for eight weeks, 48 sedentary pregnant women and 40 sedentary non-pregnant women. The measurement of spinal curvatures took place at the beginning and the end of the study using with flexible ruler of mark Morn sun. The results showed that thoracic kyphosis and lumbar lordosis have increased and are significantly different between the three groups. These results suggest that prenatal gymnastics during pregnancy acts on the curvatures of the spine minimizing their emphasis. Summary During pregnancy, the female body undergoes postural changes. These changes can impact on physical health and lead to limitations during everyday activities. This study evaluated the effect of prenatal gymnastics program on changes in spinal curvature in pregnant women in Porto-Novo. The sample was comprised of 120 women recruited purposive and divided into three groups: 32 pregnant women using antenatal gymnastics twice a week for eight weeks, 48 sedentary pregnant women and 40 non-sedentary pregnant women. The measurement of spinal curvature was carried out at the beginning and end of the study using a flexible rule Morn sun brand. The resultant obtained show that thoracic kyphosis and lumbar lordosis increased and are significantly different between the three groups. These results suggest that prenatal gymnastics during pregnancy acts on the curvatures of the spine minimizing their emphasis.e curvatures of the spine minimizing their emphasis.
Keywords: Pregnant woman; Spine; Prenatal gymnastics; Benin